Expert system in determining the quality of nutmeg breed using website-based forward chaining methods - Muslihudin M.; Sathesh Kumar K.; Ilayaraja M.; Shankar K.; Lailaturrohmah; Putra D.P.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
?Abstract: The need for information about datermining quality nutmeg seedlings is currently needed, This usually occurs in areas far from settlements one of which is farmers located in rural areas far from technological developmebts. The lack of experts or experts in the surrounding environment has increasingly triggered crop failure due to lack of knowledge. by building expert systems whose data is obtained from experts so that the system built has the ability to provide solutions such as an expert who is an expert in their field. This process continues until it reaches a goal or there are no rules whose premise matches the known facts. Media system maker application uses the language of PHP and MySQL as a database. Therefore the authors will review about how to choose quality and superior nutmeg seedlings, the implementation of an expert system to determine the quality of nutmeg seedlings is expected to provide easy access for users, through the use of website-based media tools. BEIESP.